2011
DOI: 10.4103/2152-7806.80115
|View full text |Cite
|
Sign up to set email alerts
|

Amebic encephalitis

Abstract: Background:Amebic encephalitis (granulomatous amebic encephalitis, GAE) an extremely rare disease occurring in immunocompromised patients. Presentation and early imaging findings are nonspecific. In GAE, enhancement may or may not be seen on imaging studies despite the presence of an aggressive, necrotizing, parasitic infection.Case Description:The patient was a 79-year-old man with ill-defined autoimmune hepatitis. He was on mild immunosuppression with 6-MP and low-dose prednisone. He presented with an acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 19 Amoebic encephalitis has a mortality rate of over 90% with no established effective treatments, although there may be some potential options for certain organisms, 19 22 and is often a post-mortem pathological diagnosis. 11 , 20 Imaging diagnosis is difficult, but our review of the findings in published case reports revealed some “typical” features such as hypointensity on T 1 weighted MRI, hyperintensity on T 2 weighted MRI, contrast enhancement, haemorrhage, oedema and mass effects, but these are not definitive and were not observed in all cases. Furthermore, differential diagnoses such as encephalitis from a different pathogen (viral, bacterial, etc.)…”
Section: Discussionmentioning
confidence: 90%
“… 19 Amoebic encephalitis has a mortality rate of over 90% with no established effective treatments, although there may be some potential options for certain organisms, 19 22 and is often a post-mortem pathological diagnosis. 11 , 20 Imaging diagnosis is difficult, but our review of the findings in published case reports revealed some “typical” features such as hypointensity on T 1 weighted MRI, hyperintensity on T 2 weighted MRI, contrast enhancement, haemorrhage, oedema and mass effects, but these are not definitive and were not observed in all cases. Furthermore, differential diagnoses such as encephalitis from a different pathogen (viral, bacterial, etc.)…”
Section: Discussionmentioning
confidence: 90%
“…Most published cases have used multiple drug combinations with varying success. [ 1 2 4 6 8 9 10 11 12 13 15 16 17 18 20 23 ] A review of the English language literature for cases of CNS infection with Acanthamoeba diagnosed antemortem since 2000 and which described treatment protocols is summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The appearance correlates with intense inflammation caused by trophozoites at histopathologic examination that leads to extensive necrosis and hemorrhage, findings frequently noted in postmortem whole brain sections (109). Ring-enhancing lesions in the brain have been reported in Acanthamoeba infections (114). Ranjan et al (100) described a case of Acanthamoeba infection in an interhemispheric ependymal cyst.…”
Section: Primary Amebic Meningoencephalitismentioning
confidence: 96%